2020
DOI: 10.1177/0300060520970763
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcal endocarditis of native valves without immunodeficiency or drug abuse: a case report

Abstract: Cryptococcal endocarditis has rarely been reported. Most patients with this condition are associated with risk factors, such as structural heart disease/valve replacement, immunodeficiency/immunosuppression or drug abuse. We report a case of cryptococcal endocarditis of the native valves without any risk factors. A 50-year-old Chinese man was admitted to hospital with fever for 1 month without any underlying heart disease, immunodeficiency, or drug use. He was diagnosed as having Cryptococcus neoformans infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…C. neoformans is typically known to cause serious central nervous system that infections, most commonly causing meningitis with lung and skin infections [ 4 ]. In one study, conditions associated with Cryptococcal infection in non-HIV individuals included immunosuppressive drug treatment (41%), SLE (16%), malignancies (16%), and diabetes mellitus (14%) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…C. neoformans is typically known to cause serious central nervous system that infections, most commonly causing meningitis with lung and skin infections [ 4 ]. In one study, conditions associated with Cryptococcal infection in non-HIV individuals included immunosuppressive drug treatment (41%), SLE (16%), malignancies (16%), and diabetes mellitus (14%) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cryptococcal endocarditis is extremely rare and hence is not extensively studied in the literature. A study published in 2020 identified 12 published cases and another case report was described in 2021 [ 4 , 5 ]. Unlike most of the previously reported cases of cryptococcus endocarditis , our case occurs in a patient without a history of underlying valvular pathology or a prosthetic valve.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations